Work-Life Balance and Its Impact on the Performance Effectiveness of Police and ASN Polri Biddokkes Polda Kalsel: The Role of Employee Engagement - Ani Purwaningsih; Rini Rahmawati (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Abstract This study aims to determine the effect of Work-Life Balance, Employee Engagement, and Employee Performance on the Police and ASN Polri at Biddokkes Polda Kalsel; this type of research uses quantitative methods where the data shows responses/values from respondents who measure the effect of Work-Life Balance, Employee Engagement, Employee Performance. The data collection method uses questionnaires and library research, then with the Population of this study, as many as 79 respondents consisting of Police and ASN Polri at Biddokkes Polda Kalsel. This research was conducted with analysis Techniques using the Partial Least Square Model and t-test with the SMART PLS V.3.29 tool. From the results of this study, it was found that Work-Life Balance has no effect on Employee Performance, Work-Life Balance has a significant impact on Employee Engagement, and Work-Life Balance substantially affects Employee Performance through Employee Engagement. Keywords: Work-Life Balance, Employee Engagement, Employee Performance.